Chronic sternal osteomyelitis complicating primary manubriosternal septic arthritis - Sinha, S.; Sinha, A.; Nagarajah, K.; Oei, E. L.; Critchley, P.; McNally, M. A. (Clinical rheumatology, 2006)
We present a 40-year-old woman complaining of worsening chest pain. She was previously treated with a prolonged course of antibiotics for suspected sternal osteomyelitis. Radiological investigations were suggestive of ongoing inflammation within the manubriosternal joint. Formal surgical debridement yielded evidence corroborating the diagnosis although microbiological samples were negative. Prolonged empirical treatment with intravenous antibiotics leads to a complete resolution of symptoms. Primary culture-negative manubriosternal septic arthritis is rare, and suboptimal treatment, particularly if confused with other conditions such as synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome, compounds its considerable morbidity.